The Dual Mandate: Profit And Public Good In Pharmaceutical Corporations : A Critical Realist Perspective - Ahmed, Mukhtar (Journal of Critical Realism in Socio-Economics (JOCRISE), 2025)
This study explores the enduring conflict between profit motives and public health responsibilities in pharmaceutical corporations through a critical realist lens. It aims to reveal how corporate behaviors, such as pricing strategies and CSR initiatives are not random but deeply shaped by systemic capitalist structures and regulatory frameworks. Utilizing critical realism’s layered ontology (empirical, actual, and real), the analysis highlights how surface practices are driven by underlying economic imperatives, investor pressures, and intellectual property regimes. Case studies on insulin pricing and COVID-19 vaccine access demonstrate the challenges corporations face in balancing innovation with equitable healthcare delivery. Findings indicate that although some firms attempt to align business goals with societal needs, the dominant structures favor short-term profitability over long-term public benefit. The research argues that incremental reforms are insufficient and recommends systemic strategies, including patent law revisions, alternative financing mechanisms, and the incorporation of social impact metrics in corporate evaluations. By addressing root causes rather than symptoms, pharmaceutical corporations can better fulfill their dual mandate, ensuring both sustainable innovation and broader healthcare equity. A critical realist perspective thus provides a deeper understanding of why tensions persist and how more transformative changes can be achieved